Pengaruh Lokus Pengendalian, Pengetahuan Keuangan, Dan Persepsi Pendapatan Terhadap Perilaku Manajemen Keuangan Pada Generasi Milenial Di Kecamatan Cipayung Kota Madya Depok - Hasan Roseno; Kumba Digdowiseiso (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to determine the effect of locus of control, financial knowledge, income perceptions and financial management behavior as the dependent variable. The sample in this study were 155 respondents through questionnaires with simple random sampling technique. In this study, descriptive analysis and multiple linear analysis became methods for data analysis with the help of STATA statistics software version 17. The results of this study indicate that financial knowledge has a positive and significant influence on financial management behavior. Meanwhile, locus of control and perceptions of income do not have an influence on the financial management behavior of the millennial generation in Cipayung sub-district, Depok Madya city. Keywords: Locus Of Control, Financial Knowledge, Income, Financial Management Behavior.